SELF-REGULATION IN THREE TYPES OF ONLINE INTERACTION: A STUDY AT A TEACHER PREPARATION PROGRAM AMIDST COVID-19 PANDEMIC - Machdalena Vianty; Sofendi Sofendi; Zahra Alwi; Didi Suhendi (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2023)
Having done the online learning mode for the conduct of teaching and learning activities for more than a year as the impact of covid-19 pandemic, this article presents a report on how the students have managed their learning. Specifically, this present study was aimed to describe the three aspects of self-regulation in three types of online interaction: students’ self-regulation in interaction between them and content; students’ self-regulation in interaction between them and their teacher; and students’ self-regulation in interaction between them and their peers. In addition, this present study also looked at the correlation between self-regulation and the students’ academic performance and find out which aspect was significantly correlated with the academic performance. Involving 205 students of a teacher preparation program as the participants and used the Online Self-Regulated Questionnaire (OSRQ) to collect the data, it was found that the average mean score for the online interaction was above 5, suggesting that the students tended to agree with the statements in the three types of online interaction. The finding also revealed that a weak and positive, but not significant correlation existed between the students’ self-regulation of online interaction and their academic achievement.